Decrease in aerial challenges after revision of goal kick rules in Japan Professional Soccer League: explorative study of the possibility of a risk reduction for head injury, concussion, and brain damage by a rule revision - Shibukawa, K.; Hoshikawa, Y. (Science and Medicine in Football, 2024)
In 2019, FIFA revised the goal kick (GLK) rule such that a GLK could be performed even if the kicker had teammates in the penalty area. This study aimed to examine whether the rule revision reduced the frequency of aerial challenge (AC) and long GLKs (LGLKs), which are risk factors for head injury and concussion in soccer. We analyzed all official league matches (306 matches/season) of the Japan Professional Soccer League 1st Division before (2018 season) and after the rule revision (2020 season). The analysis categorized GLKs into short GLKs (SGLKs) and LGLKs, depending on the GLK distance, and included the frequency and causes of AC, in each match following a GLK, which were compared between the 2018 and 2020 seasons. The average number of LGLKs per match in the 2020 season (8.85) decreased compared to that in the 2018 season (14.20). Additionally, for ACs following a GLK, the frequency of ACs decreased from 6.08 to 3.92 per match. Meanwhile, the frequency of LGLKs tended to increase toward the end of the first and second halves in matches. The results of this study revealed that the 2019 GLK rule revision reduced the number of LGLKs and ACs.